Case Report: Metagenomic next-generation sequencing diagnosed a rare case of sternal tuberculosis mimicking a malignant tumour - Huang, Jiawei; Lan, Cong; Liang, Yunjie; Chen, Huilong; Liang, Hanping; He, Haiquan; Che, Siyao; Chen, Ying (Frontiers in Medicine, 2026)
This is a case report of a 17-year-old female patient who presented with a painless, palpable swelling on the anterior chest wall. Imaging studies revealed osteolytic lesions involving the manubrium and adjacent ribs, along with multiple enlarged lymph nodes, raising a high suspicion of malignant tumour with metastasis. An ultrasound-guided needle biopsy revealed the pathological finding of “granulomatous inflammation.” Multidisciplinary consultation and clinical indicators, including a strongly positive purified protein derivative (PPD) test and markedly elevated erythrocyte sedimentation rate, were taken to indicate a potential diagnosis of tuberculosis. Consequently, subsequent metagenomic next-generation sequencing (mNGS) of the biopsy specimen identified nucleic acid sequences belonging to the Mycobacterium tuberculosis complex, thereby confirming the rare diagnosis of sternal tuberculosis. Following the administration of standardised anti-tuberculosis therapy, a substantial reduction in the size of the lesion was observed, thereby validating the accuracy of the diagnosis. This case underscores the importance of considering extrapulmonary tuberculosis in the differential diagnosis of bone-destructive lesions and demonstrates the critical value of mNGS technology in confirming challenging infectious diseases.